Consumer perspectives on pharmacy staff roles in providing oral health services in Australia. (28th October 2019) - Pateman, Kelsey; Huang, Jialin; Ford, Pauline J.; Mutch, Allyson; Freeman, Christopher R.; Taing, Meng‐Wong
Abstract: Australian and international findings report pharmacy staff are motivated to expand and undertake new roles in public health and expressed a strong interest in providing oral healthcare services to the community. We sought to describe consumer experiences within primary oral healthcare, and views about pharmacy staff roles and boundaries in providing oral health services as perceived by a sample of consumers living within metropolitan Australia. Sampling occurred purposively to enable diverse perspectives on the topic. Socioeconomic status, as defined by the Socio‐Economic Index for Areas, was used as the primary criteria to stratify focus group recruitment. Thematic, in‐depth analysis of focus group discussions was carried out. In all, 34 participants took part in six focus groups, held in metropolitan settings in Queensland, Australia. Findings show that consumers supported pharmacy staff performing non‐invasive oral health services including providing oral health education and advice, reviewing medications and recommending evidence‐based medications. As services became more invasive (i.e., oral screening and fluoride application), questions and concerns were raised around the appropriateness of the community pharmacy setting and the level of training of pharmacy staff to provide these services. This study identifies the need to support greater integration of oral healthcare roles by community pharmacy staff. Future innovative and collaborative research involving additional stakeholder groups are necessary to explore, develop and test the feasibility and effectiveness of pharmacy‐led oral healthcare models.